Устройство для очистки и легирования поверхности полупроводника - Иващук, А.В.; Кохан В.П. (Технология и конструирование в электронной аппаратуре, 2000)
Предложено устройство и технология обработки поверхности полупроводника в едином технологическом цикле с нанесением металлизации барьерных и омических контактов. The device design has been presented and technology of GaAs surface treatment with low energy argon ions followed by barrier or ohmic contacts in the single vacuum cycle without discapsulation of evaporation chamber has been described. It is shown that barrier contacts fabricated by the use of proposed technology process have the improved electrical parameters and thermal stability.